2016
DOI: 10.2459/jcm.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Does patient–prosthesis mismatch after aortic valve replacement affect survival and quality of life in elderly patients?

Abstract: PPM after AVR does not affect survival, functional status, and QoL in patients aged at least 75 years. Surgical procedures, often time-consuming, contemplated to prevent PPM, may therefore be not justified in this patient subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
1
17
0
3
Order By: Relevance
“…There are two types of questionnaires: generic and disease-specific. One of the most widely used generic health status instruments to assess HRQoL is the Medical Outcomes Study Short Form (SF-36) questionnaire and it has been studied in many populations, also in patients with CAD and valvular heart disease [5][6][7][8][9]. Many studies have shown that coronary artery bypass grafting (CABG) is a favorable method of revascularization in patients with multivessel CAD (MVCAD).…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of questionnaires: generic and disease-specific. One of the most widely used generic health status instruments to assess HRQoL is the Medical Outcomes Study Short Form (SF-36) questionnaire and it has been studied in many populations, also in patients with CAD and valvular heart disease [5][6][7][8][9]. Many studies have shown that coronary artery bypass grafting (CABG) is a favorable method of revascularization in patients with multivessel CAD (MVCAD).…”
Section: Introductionmentioning
confidence: 99%
“…PPM is a common finding after AVR. It is mostly mild to moderate, with incidence ranging in studies from 20% to 70%, while severe PPM is rare (2%-11% in studies) (2,(5)(6)(7)(8). In our study, 57% pts had PPM, categorized as mild to moderate.…”
Section: Discussionmentioning
confidence: 41%
“…PPM is generally a relatively common finding, found in up to 70% AVR procedures (2,(5)(6)(7)(8). If the EOA/BSA ratio is <0,85cm2/m2, PPM is defined as mild or moderate, and as severe if the EOA/BSA ratio is <0,65cm2/m2 (2).…”
Section: Impact Of Mild Patient Prosthesis Mismatch On Quality Of Lifmentioning
confidence: 99%
See 1 more Smart Citation
“…В условиях постоянного и устойчивого роста количества оперативных вмешательств у пациентов пожилого возраста несомненна необходимость анализа как социально-адаптивного, так и психологического и физического состояния пролеченных. Улучшение качес-тва жизни пожилых пациентов, подвергшихся протези-рованию аортального клапана, продемонстрировано раз-ными авторами [16][17][18]. Анализ качества жизни пациента ставит во главу угла лечение пациента, а не заболевания.…”
Section: Discussionunclassified